Arachidonic acid promotes skin wound healing through induction of human MSC migration by MT3-MMP-mediated fibronectin degradation - Oh, S Y (Cell Death Dis, 2015)
Arachidonic acid (AA) is largely released during injury, but it has not been fully studied yet how AA modulates wound repair with stem cells. Therefore, we investigated skin wound-healing effect of AA-stimulated human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) in vivo and its molecular mechanism in vitro. We found that transplantation of hUCB-MSCs pre-treated with AA enhanced wound filling, re-epithelization, and angiogenesis in a mouse skin excisional wound model. AA significantly promoted hUCB-MSCs migration after a 24 h incubation, which was inhibited by the knockdown of G-protein-coupled receptor 40 (GPR40). AA activated mammalian target of rapamycin complex 2 (mTORC2) and Akt(ser473) through the GPR40/phosphoinositide 3-kinase (PI3K) signaling, which was responsible for the stimulation of an atypical protein kinase C (PKC) isoform, PKCζ. Subsequently, AA stimulated phosphorylation of p38 MAPK and transcription factor Sp1, and induced membrane type 3-matrix metalloproteinase (MT3-MMP)-dependent fibronectin degradation in promoting hUCB-MSCs motility. Finally, the silencing of MT3-MMP in AA-stimulated hUCB-MSCs failed to promote the repair of skin wounds owing to impaired cell motility. In conclusion, AA enhances skin wound healing through induction of hUCB-MSCs motility by MT3-MMP-mediated fibronectin degradation, which relies on GPR40-dependent mTORC2 signaling pathways.